Effect of the Injection moulding processing conditions on biopolymers final properties - Teixeira, Pedro (2011)
This research work intended to study the effect of the main injection moulding parameters in the final properties of biopolymers mouldings. An experimental procedure was carried out in which four biopolymers containing different composition percentages of poly-lactic acid (PLA) and plasticized starch (PLS) were compared with polypropylene (PP). For each material the effect of the processing conditions (mould temperature, injection temperature and holding pressure) on the final properties was discussed and the possibility of using biopolymers as a substitute of PP in household utility products was evaluated.